A longitudinal study of academic self-concept in a streamed setting: home environment and classroom climate factors - Liu, Woon Chia. (2000)
The effect of streaming on students' academic self-concept and their perceptions of home environment and classroom climate was examined in a 3-year longitudinal study of a single cohort in Singapore. The subjects were 495 Secondary 1 (average age 13) students, who were streamed based on their Primary School Leaving Examination results taken at the end of Primary 6 (average age 12). The study was conducted with the use of a self-constructed questionnaire on four occasions at approximately 1-year intervals. The measures included the academic self-concept scale, made up of the students' confidence and students' effort subscales, the home environment scale, made up of the relationship with parents and academic support subscales, and the classroom climate scale, made up of the relationship with teachers, teachers' expectations and peer relationship subscales. The results revealed that the students' academic self-concept, and their perceptions of home environment and classroom climate largely declined from Secondary 1 to Secondary 3, and the declines were more pronounced for the higher-ability stream students than the lower ability stream students. In addition, the lower-ability stream students' academic self concept and their perception of classroom climate were more negative than those of their higher-ability stream counterparts immediately after streaming. Nonetheless, they were comparable if not more positive than those of their higher-ability stream counterparts three years after being streamed. Furthermore, regression analyses revealed that perceived teachers' expectations, relationship with teachers, relationship with parents and parental academic support were main predictors of students' academic self-concept. However, parental academic support tended to affect higher-ability stream students' academic self-concept more than that of their lower-ability stream counterparts, whilst teachers' expectations tended to affect the lower-ability stream students' confidence level more than that of their higher-ability stream counterparts.